Role of postoperative serum thyroglobulin as a prognostic factor for the outcome of radioactive iodine therapy of follicular thyroid cancer. - Selma Agić-Bilalagić; Šejla Cerić; Amela Begić; Azra Durak-Nalbantić; Edina Đozić; Timur Cerić (Medicinski glasnik, 2025)
Aim: To investigate the relationship between postoperative serum thyroglobulin level ​​and outcome of therapy with I-131 of follicular thyroid cancer. Methods: A total of 106 patients with follicular thyroid cancer who were being treated and monitored at the Clinic for Nuclear Medicine at Clinical Center of the University of Sarajevo were included. The inclusion criteria were: surgery of total thyroidectomy, histopathological diagnosis of follicular thyroid cancer, and applied therapy with radioactive iodine. Exclusion criteria were patients with incomplete data, who were not treated with radioidine treatment, or had a different histopathological diagnosis. Postoperative serum thyroglobulin levels were correlated with results of whole body scintigraphies after 12 months (first diagnostic scintigraphy) and whole body scintigraphies after 24 months (second diagnostic scintigraphy). Results: The higher frequency of recurrent disease in patients with elevated level of thyroglobulin was found compared to patients with lower postoperative thyroglobulin level. Elevated level ​​of postoperative thyroglobulin correlated with positive scintigraphy findings, i.e., with the occurrence of recurrence and/or metastases in patients with follicular cancer. The cut-off level of postoperative thyroglobulin for recurrence and/or metastasis, i.e. for failure of ablative therapy with I-131, was >12.6 ng/mL. Conclusion: Our study showed that level of postoperative thyroglobulin is an important prognostic factor for the outcome of radiodine therapy of follicular thyroid cancer and should be taken into account in deciding on therapy in this type of cancer in everyday practice Keywords: : prognosis, radioiodine, thyroid neoplasm, recurrence
Keywords: prognosis; radioiodine; thyroid neoplasm; recurence